Evaluation of a virtual reality based interactive simulator with haptic feedback for learning NGT placement - Vico Chung Lim Chiang; Thomas Kup Sze Choi; Shirley Siu Yin Ching; Kevin Lai Kit Leung (Halla Newcastle Education and Research Center, 2017)
Background The placement of a nasogastric tube is a blind process; the tube may be mistakenly inserted into other locations, leading to possible complications or fatal incidents. Effective education and training of nursing students to perform this procedure is essential. Purpose To investigate the application of the virtual reality based simulator with haptic feedback to nursing students for their learning around nasogastric tube placement. Methods A quasi-experimental non-equivalent group pre- and post-test study, in which the outcome measures of two classes of pre-registration nursing students were compared for their evidence of learning about the advanced NGT simulator (in addition to usual training) against the control group who only used mannequins for their usual education and training. Results There was a decrease, though remaining at a good level, in the technology acceptance rating within (p = .000) and between (p < .05) the simulator group than the control over time at post-test. Taking into consideration of some demographic differences at baseline between the two groups, analysis of results demonstrated that there was no predictor effect of those factors in relation to technology acceptance (F = .02, p = .922), but in scores for the test using multiple-choice questions (MCQ) about knowledge in nasogastric tube insertion (F = 23.4, p = .000). Both groups demonstrated significant increases in MCQ scores at post-test, with higher scores in the simulator group at both pre-test (p < .05) and post-test (p = .000). There was no significant difference in learning outcomes around competence in skills within the evaluation results between groups at post-test. Usability of the simulator system as rated by the simulator group was good. Conclusions Students did not reject the use of the new simulator for their learning about nasogastric tube placement. As an adjunct to conventional teaching and learning, the use of the simulator appears to be promising in enhancing the education and training of nursing students for development of the important clinical skill of safe nasogastric tube placement. Future studies are warranted, with the design inclusive of equivalent groups and a larger sample size to further the evidence in substantiating the use of this simulator for better learning outcomes.